FORMULASI SEDIAAN KRIM EKSTRAK ETANOL KULIT BUAH KAKAO (Theobroma cacao L.) SEBAGAI ANTIOKSIDAN - Nurul Huda; Cantika Sindi; Zipora Amelia Kusmawan; Herlando Sinaga (Universitas Cokroaminoto Palopo, 2022)
Research has been carried out on the formulation of ethanol extract cream for cocoa pods (Theobroma cacao L.). The research was carried out at the Laboratory of the Faculty of Health Sciences, Jayapura University of Science and Technology, ± 3 months, namely March 5 - June 6, 2021. The purpose of the study was to determine the best formula for Ethanol Extract Cream for Cocoa Fruit Peel. The type of this research is descriptive method with laboratory experimental approaches. The population used in this study was the Cocoa Fruit Skin in Arso III Region, Keerom Regency. The number of samples in the study was 3 kg. The basic ingredients are taken from cocoa pods and the active ingredients are taken from maceration for 3×24 hours using70% ethanol as solvent. The formulation was carried out with variations of formulas I, II, and III with concentrations of stearic acid as an emulsifier, namely 6%, 9%, 12%. To get the best formula, an evaluation of the preparation was carried out including cream type testing, organoleptic testing, homogeneity testing, pH testing, dispersion testing, stability testing, and irritation testing. The results showed that the best formula was formula III with a concentration of 12% stearic acid with organoleptic evaluation test results showing a brown color, soft texture, homogeneous preparation, pH 6.3 and spreadability of 5 cm.